Kewenangan Pemerintah Kota Ambon Terhadap Anak Korban Eksploitasi Ekonomi - Yesayas, Junet Daniela; Alfons, Saartje Sarah; Matitaputty, Merlien Irene (CAPITAN: Constitutional Law & Administrative Law Review, 2023)
The authority of the Ambon city government over child victims of economic exploitation is urgently needed, given that children are the next generation of the nation and state that must always be protected, and their growth and development is paid attention to with the rights they have which have been regulated in the Laws and Regulations. The purpose of this study was to find out and understand how the authority of the Ambon City Government for Children Victims of Economic Exploitation is in accordance with Legislation and what forms of legal protection for children who are victims of economic exploitation. The research method used is normative legal research method and is analyzed qualitatively. The results and discussion show that the Ambon City Regional Government is based on the provisions of Article 20 and Article 21 paragraph (1) to (4) of Law Number 35 of 2014 concerning Child Protection and the provisions of Article 23 paragraph (4) of Ambon City Regional Regulation Number 1 of 2019 Concerning the Implementation of Child Friendly Cities, has authority over the implementation of Child Protection, respects the fulfillment of Children's Rights, guarantees the fulfillment of Children's Rights and is responsible for formulating and implementing policies in the field of implementing Child Protection. Authority Regional Government Against Children according to Law Number 35 of 2014 concerning Child Protection includes the obligations and responsibilities of the Regional Government. However, in the Ambon City Regional Government Regulation which specifically regulates the implementation of Means of Fulfilling Legal Protection Rights for children, it does not give law enforcement authority to the Regional Government against the perpetrators.